Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Hand Body Lotion Vaseline Pada UHN Medan - Simanullang, Angel Natalia; Sihombing, Natalia E.; Sinaga, Kepler (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to determine whether or not there is an influence of Brand Image and Price on Purchasing Decisions of Vaseline Hand Body Lotion products on UHN Medan students. This study uses a quantitative method where the data collection technique uses a questionnaire. The population of this study was 3,317 people and the number of samples selected using the Slovin formula was 97 people. Based on the results of the hypothesis test, it can be concluded that the significance value of Brand Image (X1) = 0.000 <0.05 or tcount = 5.504> ttable 1.984 or H0 is rejected and H1 is accepted and the significance value of Price (X2) = 0.000 <0.05 or tcount = 8.947> ttable 1.984 or H0 is rejected and H1 is accepted. This means that Brand Image and Price have a partial effect on purchasing decisions. The significance value of variables X1 and X2 is 0.000 < 0.05 and the Fcount value is 39.617> Ftable 3.09 or H0 is rejected and H1 is accepted, meaning that Brand Image (X1) and Price (X2) have a simultaneous effect on Purchasing Decisions (Y).